Commensal bacteria of the lung microbiota synergistically inhibit inflammation in a three-dimensional epithelial cell model - Goeteyn, Ellen; Grassi, Lucia; Van den Bossche, Sara; Rigauts, Charlotte; Vande Weygaerde, Yannick; Van Braeckel, Eva; Maes, Tania; Bracke, Ken R.; Crabbé, Aurélie (Frontiers in Immunology, 2023)
Patients with chronic lung disease suffer from persistent inflammation and are typically colonized by pro-inflammatory pathogenic bacteria. Besides these pathogens, a wide variety of commensal species is present in the lower airways but their role in inflammation is unclear. Here, we show that the lung microbiota contains several species able to inhibit activation of the pro-inflammatory NF-κB pathway and production of interleukin 8 (IL-8), triggered by lipopolysaccharide (LPS) or H2O2, in a physiologically relevant three-dimensional (3D) lung epithelial cell model. We demonstrate that the minimal dose needed for anti-inflammatory activity differs between species (with the lowest dose needed for Rothia mucilaginosa), and depends on the type of pro-inflammatory stimulus and read out. Furthermore, we evaluated synergistic activity between pairs of anti-inflammatory bacteria on the inhibition of the NF-κB pathway and IL-8 secretion. Synergistic anti-inflammatory activity was observed for 4/10 tested consortia. These findings indicate that various microbiota members can influence lung inflammation either alone or as a consortium. This information can contribute to a better understanding of the lung microbiota in chronic lung disease development and progress, and could open up new avenues for treatment.